U.S. Special Operations Forces in the Philippines, 2001–2014 - Robinson, Linda; Johnston, Patrick B.; Oak, Gillian S. (RAND Corporation, 2023)
This report examines the 14-year experience of U.S. special operations forces in the Philippines from 2001 through 2014 and the activities and effects of special operations capabilities employed to address terrorist threats in Operation Enduring Freedom—Philippines through training and equipping Philippine security forces, providing operational advice and assistance, and conducting civil–military and information operations.